Exploring Grapevine Phenology and High Temperatures Response Under Controlled Conditions - Merrill, N. K.; García de Cortázar-Atauri, I.; Parker, A. K.; Walker, M. A.; Wolkovich, E. M. (Frontiers in Environmental Science, 2020)
Climate change has challenged growers and researchers alike to better understand how warm temperatures may impact winegrape plant development across varieties. Yet multi-variety studies present challenges. Here we review studies of controlled warming on winegrape varieties alongside a new study of the budburst and flowering phenology of 50 varieties of Vitis vinifera subsp. vinifera in the lab, with a small set of plants exposed to higher temperatures (20, 26, 30, 34, 37°C mean temperatures in growth chambers) during flowering. We found few studies have examined more than one variety, which may be due to the challenge of growing diverse varieties together. Indeed, we found high variability in flowering success across varieties in the lab (28 out of 50 varieties had no flowering), which made it impossible to study variety-specific response to temperature. Across varieties, however, we found results in line with our literature review: higher temperatures did not have a significant effect on the rate at which vines progressed through the flowering stage, but higher temperatures did correlate with flower abortion. These results suggest a potential decrease in winegrape yields in a warmer climate due to flower abortion, but also highlight the challenges of understanding heat responses across many varieties.